In vitro T-cell responses to beta-lactam drugs in immediate and nonimmediate allergic reactions. - Luque, Inmaculada; Leyva-Fernández, Laura; Torres-Jaén, María Josefa; Rosal, Manuel; Mayorga Mayorga, Cristobalina; Segura, José Manuel; Blanca, Miguel; Juárez, Carlos (Wiley, 2001)
Background: Beta-Lactam drugs may induce both cellular and humoral allergic reactions, and there is evidence that T cells play an important role in the pathogenesis of these reactions. The aim of this work was to assess the sensitivity and specificity of the lymphocyte transformation test (LTT) as an in vitro diagnostic tool, in patients with either an immediate or a nonimmediate reaction to penicillin G and/or amoxicillin. Methods: Fifty patients with a well-documented history of allergic reactions to beta-lactams (31 immediate and 19 nonimmediate) were studied by means of skin tests (prick and intradermal), radioallergosorbent test (RAST), and, when necessary, controlled administration of the drug. Twenty-eight healthy subjects with good tolerance to penicillins served as controls. LTT was performed in all subjects. Results: Skin tests were positive in 77.4% of the patients with immediate reactions and in 36.8% of those with nonimmediate reactions. The overall sensitivity of LTT in the allergic patients was 62%, but, when analyzed separately, sensitivity was 64.5% for the immediate group and 57.9% for the nonimmediate group. The LTT specificity was 92.8%. Conclusions: The LTT should be considered a useful in vitro diagnostic tool to identify subjects allergic to penicillins, especially patients with nonimmediate reactions where the LTT has a better diagnostic value than skin tests. Interestingly, positive T-cell proliferative responses can be observed 10 or more years after the occurrence of the reaction without further exposure to the drug.
T-cell responses to beta-lactam drugs.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3704?template=romeo
Keywords: Alergia a los medicamentos; Antibióticos - Efectos secundarios; Drug allergy; Beta-lactams; T cells; Lymphocyte transformation test; Skin tests